An assessment of e-tolling as a method of financing Gauteng roads - Ponter, Lloyd Anthony (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
E-tolling was recently implemented on roads in Gauteng, South Africa. This gave rise to a great deal of protest by road users and a court battle between the South African National Roads Agency (SANRAL) and the Opposition to Urban Tolling Alliance, a body representing road users. The e-tolling system was criticised at various levels and on numerous grounds, some financial and others appearing to be emotional. This thesis attempted to analyse the various grounds for objection against the system, the main goal of the research being to analyse e-tolling in Gauteng to ascertain whether or not the introduction of e-tolling was justified or whether an alternative method of taxation to pay for the upgrading of Gauteng roads would have been more cost-effective. Secondary data in the form of documents from multiple sources was used in the analysis, including an Economic Impact Assessment that was one of the key inputs into the decision to introduce e-tolling. It was found that there are multiple problems plaguing the e-toll system and e-tolling is not the most cost-effective taxation method of paying for Gauteng roads. Using a fuel levy or general tax revenue available to the National Treasury were both found to be more cost-effective methods as they would have achieved the same result (repairing and upgrading specific Gauteng roads), at a cost of R20,0913 billion less than e-tolling. It was suggested that the best taxation method/s to pay for the roads would have been using a fuel levy and general tax revenue as the primary funding methods, with vehicle licensing fees and long distance toll roads as secondary methods to aid the primary methods.
Keywords: Toll roads -- Taxation -- South Africa -- Gauteng; Electronic Road Pricing System -- South Africa -- Gauteng; Toll roads -- South Africa -- Gauteng -- Cost effectiveness